40 ans de recherche en plein air : évolution et tendance. Issue 1 (2nd January 2018) - Branget, Benjamin; Auger, Denis; St-Laurent, Maude
Abstract : Over the past 40 years, outdoor recreation research has developed a solid theoretical foundation that has allowed a better understanding of this field of study. This theoretical base has also allowed the development of conceptual models that have lent a fascinating intellectual framework to outdoor recreation research. Between 1978 and 2017, Loisir et Société/Society and Leisure published more than 960 articles; of these, 64 were related to outdoor recreation. These articles have illustrated the evolution and maturation of research in outdoor recreation. This can be observed through the evolution of the articles' theoretical and conceptual frameworks, methodological approaches and themes studied. In addition, the various themes and frameworks can be grouped under three essential dimensions of outdoor recreation research : nature and territory, human and "human" activities, and sustainable development of resources. All the dimensions, issues and trends have an impact on the research, management and development of outdoor recreation.